Literature in the landscape: designing public parks to encourage outdoor exploration, activity and reading for elementary school-aged children - Rose, Katelyn (Kansas State University, 2017)
Landscape architects have an opportunity to design outdoor environments that promote exploration and physical activity for elementary school students in an effort to combat childhood obesity and nature deficit disorder, while reinforcing the importance of reading. By layering themes from classic children’s literature into the landscape surrounding the Andover Public Library, a landscape was designed where children can explore physically and intellectually while being active in the outdoor environment. Research has identified the importance and benefits of outdoor exploration, activity and reading for elementary school students. Interviewing teachers and librarians about classic children’s literature and how they commonly use it helped inform my research efforts in choosing timeless and well-known pieces of children’s literature. Completing a site inventory and analysis of Andover Central Park, which surrounds the Andover Public Library, informed my site design process. The intent of my site design is to explore ways of incorporating children’s literature into a play landscape that provides opportunity for exploration and physical activity in nature.
Keywords: Children's literature; Nature deficit; Physical activity